Preparation of a Canola-based Polyethyleneimine-crosslinked Bioadhesive for Particleboards Production - Lawrence Tene Tayo; Fabian Dönni; Markus Euring (BioResources)
Over the past decades, consistent efforts have been dedicated to addressing the challenge of low performance of protein-based wood adhesives. This study explored the potential of polyethyleneimine (PEI) as a crosslinker for improving the bonding strength of canola protein isolate (CPI) and canola meal (CM) bio-adhesive. Simultaneously, the effect of the pH value of the slurry was investigated. Three-layer particleboards were manufactured using the canola-based adhesives and subjected to testing for their internal bonding strength (IB), bending strength (BS), and modulus of elasticity (E-modulus). Results showed that, despite the low PEI ratio utilized, notable enhancements in the mechanical properties of the boards were observed. The IB values increased by 17% and 15% for CPI and CM-based adhesive formulations, respectively; while the BS exhibited rose by 13% and 9%, respectively. It was observed that an increase in pH contributed to enhanced bonding properties of the bio-based adhesive. By enhancing the denaturation of the protein and increasing the free reaction group in the protein chain, this improves the crosslinking mechanism of PEI, leading to improved mechanical properties.